Polycomplex Carrier for Buccal Mucoadhesion Delivery of Metronidazole - R. I. Moustafine; V. V. Budnikov; S. G. Abdullina; Sh. F. Nasibullin; R. A. Saleev (Разработка и регистрация лекарственных средств, 2020)
Introduction. One of the well-known requirements for buccal drug delivery systems is the demonstration of mucoadhesive properties of the carrier, ensuring retention on the mucosa for a long time with the gradual release of the included drug. It should be noted that one of the advantages of buccal systems compared with oral ones is the absence of the «first pass effect» through the liver.Aim. To carry out a physicochemical and pharmaceutical research of the interpolyelectrolyte complex (IPEC), obtained on the basis of pharmaceutically acceptable polymers – Eudragit® EPO and Noveon® AA-1, in comparison with the physical mixture and individual polymers, as a mucoadhesive delivery system of metronidazole for the treatment of periodontal diseases.Materials and methods. Obtained on the basis of a pair of pharmaceutical polymers (Eudragit® EPO and Noveon® AA-1), two IPEC samples were characterized by elemental analysis, FTIR spectroscopy, and modulated temperature differential scanning calorimetry (mDSC) in comparison with individual polymers and their physical mixtures. The study of swelling ability, bioadhesion and release was carried out in a medium simulating artificial salivary fluid (pH 7.0) at a temperature of 37 ± 0.1 °C. Mucoadhesion of polymer samples and IPEC was studied using a TA.XTplus texture analyzer (Stable Micro Systems, UK). The release of metronidazole (MD) from matrices based on the developed IPEC was studied on a CE 7Smart USP 4 apparatus (Sotax, Switzerland) using the Flow Trough Cell method at a speed a flow of 20 ml/min in an open cycle within 5 hours. The amount of released MD was estimated by UV spectrophotometry on a Lambda 25 instrument (PerkinElmer, USA) at a wavelength of 319 nm.Results and discussion. As a result of studies on the physicochemical and pharmaceutical properties, there was selected the optimal composition of a polycomplex carrier (IPEC 2) based on Eudragit® EPO and Noveon® AA-1, which is characterized by the required bioadhesive properties and the ability of providing controlled release of drug from the tablet matrix (with weight ratio MD/IPEC-2 1:0.5) in conditions mimicking oral cavity environment, which provides the necessary mode of buccal delivery of metronidazole in accordance with Fick's law of diffusion.Conclusion. IPEC 2 is a perspective for use as carrier for buccal controlled delivery of metronidazole.